Effect on climate factor towards bagworm population in oil palm plantation / Nur Syaqilla Wasmin - Wasmin, Nur Syaqilla (Faculty of Plantation and Agrotechnology, 2017)
Oil palm (Elaeis guineensis) industry is the largest industry in Malaysia. However, there are several factors that contribute to decreasing in production. The bagworm is the most serious insect in the oil palm trees especially in Malaysia and it caused decreasing yields of the oil palm in range 20 percent to 30 percent. Basically, the bagworms was attacked at the frond and finally the frond become skeleton. Thus, the objective of this study to investigate such effect of climate factor toward population of bagworm in oil palm plantation, by review the bagworm population according the several temperature and rainfall distribution. Most of the finding revealed the Pteroma pendula has ability to survive in very wet weather (>200mm rain per month) compare than Metisa plana. The comparison of monthly rainfall with the infestation did not show any association. The result was confirm not significant differences through correlation analysis. But from the previous study showed that the percentage of infestation with the various ranges of rainfall per month showed that the M. plana species survive with dry weather condition. While, P. pendula, the infestation will increase from 1.9 percent to 41.5 percent when the rainfall distribution increase. Differ than temperature, these species of bagworm was showed the negative correlation between the periods of a developmental stage. Both species significantly decrease when temperature increase above 30℃. This review are indicate that climate factor can affect the bagworm population in oil palm plantation and it also can be influence by physiological of bagworm.